Integrated capacitor array effect on the ferroelectric properties for SrBi2Ta2O9 thin films fabricated by the radio frequency magnetron sputtering deposition technique - Lee, JK; Kim, TS; Jung, HJ; Cho, KJ; Park, JW; Kim, HJ (KOREAN PHYSICAL SOC, 1998)
SrBi2Ta2O9 thin films were successfully grown on the 4 inch wafer scale platinized silicon wafer by using the radio frequency magnetron sputtering system. Top electrode of platinum was dry etched and interlevel was covered by SiO2, and then, platinum upper electrode was connected with aluminum plug. Cell structure shows the delamination between SBTO layer and SiO2 layer. Small sized capacitors show degraded polarization values due to the integration process damages. It was suggested that the damage during integrating process will cause the degradation of the ferroelectric properties.
Keywords: FATIGUE